AN ANALYSIS OF STUDENTS’ AND TEACHER’S PERCEPTION ON ENGLISH ONLINE LEARNING - Nurul Amirah Siregar; Deasy Yunita Siregar (UIN Sumatera Utara, 2021)
This research was aimed to find out the students’ and teacher’s perceptions of English online learning. This research was conducted by using Descriptive Qualitative Research. The technique of analyzing data researcher used three steps, there are: 1) data reduction, 2) data display, 3) conclusion.. The findings from the data analysis shows that students gave positive perception of English online learning where students said that the process of learning English is easier with online learning and English online learning can foster students’ independent learning attitudes but students found problem in implementing online English learning because limited of internet quota during this pandemic, not everyone has enough money to buy an internet quota. Teacher also gave a positive perception of English online learning in case of the process of learning. English online learning is not effective because teacher teach virtually in one place and students follow learning from other computers in different places, it will make it difficult for students to accept and achieve learning objectives. Therefore, in their opinion,s learning will be more effective if learning is carried out face-to-face, the delivery of learning materials is carried out directly by the teacher to students and will also be more easily accessible by students so that they can achieve the desired learning objectives.